Kebijakan Perlindungan Terhadap Pelecehan Seksual di Indonesia: Sebuah Tinjauan Kritis (International Forum of Researchers and Lecturers, 2024)
Sexual harassment is a serious issue affecting individual well-being and societal integrity. Although Indonesia has implemented various policies to protect victims of sexual harassment, their effectiveness in safeguarding victims and enforcing the law remains a primary concern, as challenges in implementation often hinder the achievement of effective protection goals. This study aims to evaluate the effectiveness of sexual harassment protection policies in Indonesia, analyze the challenges faced in implementation, and provide recommendations for improvement. The research employs a normative legal method with a document analysis approach. Data were collected through literature review, analysis of legislation, policy documents, and relevant case studies. Qualitative analysis was conducted to assess the successes and weaknesses of the protection policies. The study shows that, despite an adequate legal framework, the effectiveness of sexual harassment protection policies in Indonesia is limited by several factors. Major challenges include inconsistent law enforcement, lack of socialization and education, social stigma preventing victims from reporting, and resource limitations. Case studies indicate that many sexual harassment cases are not taken seriously, whether in the workplace, educational institutions, or domestic contexts. Sexual harassment protection policies in Indonesia require significant improvements in socialization, law enforcement training, and resource enhancement. Reforms in reporting procedures and law enforcement are also needed to increase the effectiveness of protection and ensure justice for victims. Better collaboration between the government, non-governmental organizations, and the community is necessary to create a more comprehensive and responsive protection system.